Pengaruh Waktu Pemanasan Dan Penambahan Air Terhadap Aktivitas Antioksidan Selai Buah Bit (Beta vulgaris L.) - Vivi Nuraini; Merkuria Karyantina (FoodTech: Jurnal Teknologi Pangan, 2019)
The aim of this research is to get the best heating time and the amount of water that must be added in making beet jam which has high antioxidant activity. The experimental design used was a completely randomized design (CRD) factorial of 2 factors with heating duration factor (A1 = 8 minutes, A2 = 10 minutes and A3 = 12 minutes) and the amount of water added (B1 = 8 ml, B2 = 12 ml, B3 = 16ml). The parameters observed included antioxidant activity, water content and hedonic test or preference. The results showed that heating time and the addition of water interacted to influence the antioxidant activity of beet jam. The best treatment is A3B3 treatment (heating time 12 minutes, addition of water 16 ml) produces the most organoleptically preferred jam in terms of flavor and aroma parameters even though in terms of texture it is less preferred.